Acetoanaerobium noterae bacteria addition in the diet on methane production and performance of sheep - Thalib, Amlius; Widiawati, Yeni (Indonesian Journal of Animal and Veterinary Sciences, 2008)
A study on utilization of Acetoanaerobium noterae to decrease enteric methane production through feeding trial using sheep has been conducted. Animals used were young, male composite breed sheep with an initial liveweight of 19.1 kg. Twenty four animals were randomly distributed into 3 groups of dietary treatment and each group consisted of 8 animals. The diet fed to the animals were elephant grass (ad libitum) and the commercial concentrate containing 16% crude protein (200 g headâ1 dayâ1). The treatments were (I). Control (K); (II). K + Cultural Preparate of A. noterae (SKAn); and (III). K + SKAn + Aksapon SR (as defaunator). Feeding trials was conducted for 12 weeks. The measurements observed were feed consumption, body weight gain, dry matter digestibility, rumen ecosystem, and enteric methane production. In vivo dry matter digestibility was measured by collecting the faeces and urine of the animals kept in metabolism cages for 7 days effective period. The results showed that effectivity of A. noterae action as methanogenesis inhibitor was improved when it was combined with defaunator. Compared to control treatment, the treatments of SKAn with and without Aksapon SR could significantly improve (P<0.05) daily gain (increased by 21 and 32%); feed conversion ratio (decreased by 20 and 26%); enteric methane production (decreased by 15 and 20%); and the effect of SKAn on percentage composition of acetic acid in the rumen was obvious when the SKAn was combined with Aksapon SR. It is concluded that SKAn with and without Aksapon SR can be used as methanogenesis inhibitor on ruminant animals. Â  Kata Kunci: Acetoanaerobium noterae, Methane, Methanogenesis Inhibitor, Sheep